Making the biggest impact via focused product stewardship strategy for pharmaceutical device and packaging development - Meyer, Vanessa (2023)
Through increasing scrutiny regarding sustainability efforts, many pharmaceutical companies are adopting an environmental management strategy called product stewardship. Product stewardship is a sustainable manufacturing practice that aims to minimize risks, and social and environmental impacts throughout a product’s life cycle and utilizes the concept of shared responsibility. This thesis is of case study nature and deals with a pharmaceutical case department that is responsible for the design and development of pharmaceutical devices and packaging. Product stewardship has been implemented on corporate level at the case organization but not yet officially on functional level at the specific case department. Therefore, this thesis aims to develop a product stewardship strategy for the case department by first identifying a suitable strategic model for product stewardship implementation before conducting a current situation analysis and gap analysis of the case department in terms of how far the product stewardship integration has already been developed. First, a literature review of 39 academic articles and book chapters was done to identify the overall framework of product stewardship and how it is portrayed in literature. Second, a quantitative pulse survey was done in the case department to receive insights into the current level of product stewardship integration. Third, 14 semi-structured interviews with experts from device development, packaging development, leadership, and sustainability were conducted to gain further insights and establish potential themes and content for the product stewardship strategy. Lastly, the findings of the survey were integrated into the interview findings to build on the literature framework for the strategy formulation. The product stewardship strategy for the case department is built on five strategic pillars which are Design for Environment, Extended Producer Responsibility, collection & recycling, education, and collaboration & partnership as well as the prerequisite of leadership and includes a total of 12 different goals that are further split into action items for short-term, mid-term, and long-term to ensure sustainable product design and full integration of product stewardship at the case department.